Stellungnahme zur Replik von Winfried Schröder (Vechta) auf meine Kritik an der im Handbuch der Umweltwissenschaften veröffentlichten „Landschaftsökologischen Raumgliederung Deutschlands“ - Weller, Friedrich (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
My critical observation “Down-to-earth is imperative” concerning the “Landschaftsökologische Raumgliederung Deutschlands” (landscape-ecological regionalisation of Germany; Schröder et al. 2006), published in this journal in 2009 (Weller 2009), received a reply by Winfried Schröder (Schröder 2011, 2012) in which he underlines the scientificity of the method applied in his regionalisation approach and stresses its superiority compared to a more observational empiricism. The reply closes with the remarks that the critic “has not understood the statistical method which underlies the landscape-ecological regionalisation” and that his “alternative approach does not satisfy fundamental criteria of scientific work”. I have not postulated an “alternative approach” at all; I have simply contrasted Schröder’s regionalisation with a number of facts which everybody who has ever dealt with landscapes in situ can observe. Numerous examples are able to show that the regionalisation published by Schröder has in fact very little to do with the actual conditions in the field. Unfortunately, Schröder’s reply does not consider this evidence, not with a single sentence. The missing plausibility test does not seem to be a problem for the authors of this regionalisation. This is not a unique case, but an especially striking example for the kind of uncritical data analysis frequently applied in science disciplines today where the real objects get out of sight. The findings resulting from such an approach are very much in danger of being totally inadequate as a basis for practical applications – which is, after all, explicitly sought by their authors. It was my objective to point out this danger. If there had been any need for another proof of the topicality of the observation of “down-to-earth is imperative”, the distance to reality of this reply is ample evidence for this.